Identifikasi Teritori dan Perilaku pada Ruang Luar di Sekitar Gedung E, F, dan G Kampus Institut Teknologi Kalimantan - Syah Putra, Rulliannor; Dewi, Tiara Rukmaya; Rahma, Firdha Amalia Noor (SPECTA Journal of Technology, 2023)
Humans and the environment are two things that cannot be separated. Human activities require a setting or container for activities in the form of space. Various human activities are interrelated in one activity system. The container where humans carry out their activities also has a system which then the linkages of this container form a spatial layout, in this case the landscape or outer space of Buildings E, F and G, Kalimantan Institute of Technology Campus. Humans can be affected by the environment they are in and the environment can be influenced and shaped by the humans who are in it. Positive interactions between humans and the environment must be developed in the Kalimantan Institute of Technology Campus environment, so that there is harmonious harmonization between the campus environment and the academic community. Formation of a harmonious territory between humans and the environment is needed to support teaching and learning activities, interactions between campus people, to the needs of each individual such as enjoying the scenery, breathing fresh air, generating motivation, and giving a sense of enthusiasm every day. Behavior and territory formation will differ based on the reasons for the perpetrators of activities coming to campus to study or teach; the area being visited; social interaction between fellow students, students and teaching staff, as well as between lecturers; and time related. Interaction between members of the community has occurred since entering the outer space of Buildings E, F, and G which are located closest to the gates of the Kalimantan Institute of Technology Campus. With this, behavior and the occurrence of territory formation have occurred since entering the area outside of Buildings E, F, G of the Kalimantan Institute of Technology. The aim of the research is to identify the territory and behavior of students and lecturers in the outer space around Buildings E, F and G of the Kalimantan Institute of Technology. The method used in this study is a data collection method with a mapping technique based on behavior or behavior mapping. It was found that behavior is related to comfort, safety, health, accessibility, and social with environmental management recommendations.